Transport of buoyant microplastics in natural soils under rainfall or irrigation conditions - Muhammad Masood Ashiq; Peyman Babakhani; Brian Waldron; Maryam Salehi; Kati Bell; Farhad Jazaei (ENGINEERING Environment, 2026)
Microplastics (MPs) pose a significant threat to soil and groundwater quality. Yet, investigating their transport in soils has so far been limited to conventional packed column experiments where particles suspended in a stock dispersion are injected from one side of the column. This, however, does not represent the natural condition where buoyant MPs are released on the surface of the soil and storm or irrigation water induces their penetration into the soil depth. To consider such prevailing natural condition, we develop a new column experiment setup and a corresponding modeling approach to study the transport of low-density polyethylene MPs in different farmland soil types and investigate the impact of photodegradation and natural organic matter. Results revealed a substantial penetration of buoyant MPs in the soil due to the irrigation or rainfall scenarios. Mathematical modeling showed that processes such as attachment, detachment, blocking, and straining, previously observed for colloidal particles in direct injection scenarios, occur for buoyant MPs irrigation or rainfall release scenario. MPs transport increased in silt compared to the silt loam and in the presence of natural organic matter. UV-photodegraded MPs transport was greater than pristine MPs because of increased surface charge and electrostatic repulsion, reducing MPs attachment to soil.

Characteristics and risks of microplastic contamination in marine trash fish from the northern Bay of Bengal: implications for human health and local aquaculture industry - Muhammad Arifur Rahman; Md. Rakibul Hasan; Khadijatul Kubra Riya; Mohammad Abdul Baten Bhuyain; Sanjida Afrin Semme; Norhayati Ngah; Takaomi Arai; M. Belal Hossain (ENGINEERING Environment, 2026)